Global best practices on modalities for safety precausions in professional and non-professional sporting activities during Covid-19 pandemic - Awoyinfa, J. O.; Nariwoh, O. A.; Akarah, I. P. (International Journal of Scientific Research in Education, 2020)
The emergence of novel SARS-Coronavirus-2 (COVID-19) which has halted virtually all formal participation in sport and exercise since March, 2020 in Nigeria and the world in general, is a virus that originated from Chinese and has since spread across the entire globe, to the extent that consideration for reopening of event centers` including sports facilities after series of measures that were put in place by the Government at all levels to curb the spread in order to flatten the curvehas generated a lot ofgreat debate. However, Public health guidelines have begun releasing timelines for a graded reintroduction of both recreational and competitive athletics. Hence, the foremost question to those individuals with prior COVID-19 exposure/infection regarding the safety of returning to exerciseis still underinvestigation (NCAA, 2020). The World Health Organization reports that most people who contract COVID-19 (>80%), will be asymptomatic or develop mild symptoms.There are many unanswered questions with ever changing data regarding the prevalence of asymptomatic COVID-19 cases in the community, the prevalence of cardiac injury for all exposed to COVID-19 and the associated short-and long-term risks. Until there is a vaccine in place, medical experts recommend adopting specific practices including testing and social distancing when possible and having plans in place for stopping the spread in this unprecedented time of return to socialization after stretched lockdown. Based on the afore said, the researchers are of the opinion that it will be of great significance to align with global best practices in coming up with appropriate guidelines to avert possible risk with reference to the spread of Covid-19 amongst players, spectators, coaches, administrators and other members of Staff of the State Sports Councils and Commissions in Nigeria while adjusting to the new normal.